2023
DOI: 10.26603/001c.68071
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Physical Therapy Interventions for Athletes Post-Concussion: A Systematic Review

Abstract: Background Sports-related concussions are the most common cause of head injury in adolescents and young adults. Typical treatment methods for this injury include cognitive and physical rest. Evidence suggests that physical activity and physical therapy interventions can be beneficial to decrease post-concussion symptoms. Purpose The aim of this systematic review was to investigate the effectiveness of physical therapy interventions for adolescent and young adult athletes post-concussion. Study Design Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…This skill has been proven to help student athletes with self-confidence and motor skill acquisition, which can be advantageous in performance enhancement (29). A recent systematic review concluded that mental imagery exercises improved postconcussion symptoms in athletes who sustained SRC (30). In this study, two RCTs were evaluated for their rehabilitative efficacy for acute and chronic symptoms of SRC and were found to decrease postconcussion symptoms (30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This skill has been proven to help student athletes with self-confidence and motor skill acquisition, which can be advantageous in performance enhancement (29). A recent systematic review concluded that mental imagery exercises improved postconcussion symptoms in athletes who sustained SRC (30). In this study, two RCTs were evaluated for their rehabilitative efficacy for acute and chronic symptoms of SRC and were found to decrease postconcussion symptoms (30).…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review concluded that mental imagery exercises improved postconcussion symptoms in athletes who sustained SRC (30). In this study, two RCTs were evaluated for their rehabilitative efficacy for acute and chronic symptoms of SRC and were found to decrease postconcussion symptoms (30). This contradicts Arvinen-Barrow et al's (31) conclusions stating that the effectiveness of mental imagery during injury rehabilitation is indeterminate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early engagement in physical activity has been associated with reduced symptom burden at 2 weeks postinjury, faster recovery, and a lower risk of developing PSAC. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] However, the optimal volume of daily physical activity for achieving recovery in the general pediatric population remains unclear. 14 The reference standard protocol for identifying the optimal intensity of physical activity postconcussion is the Buffalo Concussion Treadmill Test.…”
Section: Introductionmentioning
confidence: 99%
“…PSAC significantly impairs daily activities and quality of life, underscoring the urgent need to generate and refine best evidence management protocols. Early engagement in physical activity has been associated with reduced symptom burden at 2 weeks postinjury, faster recovery, and a lower risk of developing PSAC . However, the optimal volume of daily physical activity for achieving recovery in the general pediatric population remains unclear …”
Section: Introductionmentioning
confidence: 99%